Governing by Objectives: Tucumán’s SDG Strategic Matrix as a Public Coordination Platform - Seiler, Cristhian Rubén (Revista del CLAD Reforma y Democracia, 2021)
Governments are continuously challenged to overcome the fragmentation of their public administrations and the disarticulation of the policies and programs they implement. In the last three decades, the nature and possible solutions to this phenomenon have aroused great concern in public management and an outstanding interest in the academic field of political and administrative sciences. Within this debate and in order to generate a contribution at the subnational levels of government, this paper argues that the strengthening and accumulation of learning within the provincial planning system can become a platform for coordination and resolution of much of the tendency towards fragmentation and disarticulation of state administrations. The strengthening of the provincial planning system and the construction of the SDG Strategic Matrix in the province of Tucumán (Argentina) show significant institutional learning in this area.
Keywords: Public Management; Planning; Management by Objectives; Coordination; Provinces; Case Analysis; Argentina